2019
DOI: 10.1108/qae-04-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of service quality on graduates’ satisfaction

Abstract: Purpose The purpose of this paper is to investigate the effect of service quality on graduates’ satisfaction as perceived by Middle East University (MEU) graduates. Design/methodology/approach This research is cross-sectional and aims to explore the effect of service quality dimensions (academic staff, administration, classrooms and library services) on graduates’ satisfaction. Data were collected from 399 graduates. After confirming validity, reliability and normality of the data, and the correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Studies have empirically verified the direct effect of student perceived service quality on student satisfaction (Teeroovengadum et al , 2019). Service quality dimensions such as academic staff, administration, classrooms, and library services affect student graduates’ satisfaction (Sharabati et al , 2019). Student perceived service quality (teaching, administrative services, academic facilities, campus infrastructure, support services and internationalisation) is the key antecedent to student satisfaction (Annamdevula and Bellamkonda, 2016).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have empirically verified the direct effect of student perceived service quality on student satisfaction (Teeroovengadum et al , 2019). Service quality dimensions such as academic staff, administration, classrooms, and library services affect student graduates’ satisfaction (Sharabati et al , 2019). Student perceived service quality (teaching, administrative services, academic facilities, campus infrastructure, support services and internationalisation) is the key antecedent to student satisfaction (Annamdevula and Bellamkonda, 2016).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Student's perception of services reflects their level of satisfaction within the institution (Subrahmanyam, 2017). Higher education institutions that achieve student satisfaction are likely to benefit in terms of student loyalty (Brown and Mazzarol, 2009), positive word of mouth (Alves and Raposo, 2009), thereby creating a competitive advantage for the institute (Wilkins and Balakrishnan, 2013; Sharabati et al , 2019). The importance of service quality and student satisfaction in literature is apparent as these constructs have garnered increased interest among researchers in Europe, followed by North America and Asia (Prakash, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Next, Hossain et al (2018) found that curriculum, teaching competence, service facility and service delivery significantly influence student satisfaction. Sharabati et al (2019) proved that faculty members, administration, classrooms and libraries had positive impacts on graduates' satisfaction.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Mattah et al (2018) examined the quality effects of physical facilities, teaching staff, administrative staff, physical environment, services and programs on student satisfaction. Furthermore, Sharabati et al (2019) investigated the effects of lecturer, administration, classroom and library quality on graduates' satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of the study is, in our opinion, influencing the architecture of the life and professional goals of young environmentalists -the readiness to overcome negative emotions in the process of interacting with the object of work. Moreover, a more accurate knowledge of the object and the subject of labour can give opportunity to correctly form the life and professional strategies of graduates and the period of study in bachelor's programs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%